Company Value Analysis Using Ratio Models Tobin’s Q at PT Gudang Garam Tbk from 2012 to 2021 - Yulianti Yulianti (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2023)
This study aims to find out what the market value, Total Liabilities, Total Assets, and company value are with the Tobin’s Q Ratio model at PT Gudang Garam Tbk for the 2012-2021 period. This type of research is quantitative. The data source used in this study is secondary data, namely the company's financial report data that has been provided by PT Gudang Garam Tbk for the 2012-2021 period. The data analysis technique used in this research is descriptive with a quantitative approach. The data analysis technique used in this study uses the Tobin’s Q firm value ratio. The results of the study show that market value is classified as capable of maximizing market value because it is relatively expensive every year. Liabilities are still able to be paid by assets. Assets are greater than liabilities. Tobin’s Q in 2012-2020 is in an Overvalued position, in 2021 it will be undervalued.